Modes of soft skills learning: a case of university information professionals' in Pakistan. Issue 8 (2nd November 2017) - Ahmad, Sajjad; Ameen, Kanwal; Ullah, Midrar
Abstract : Purpose: The purpose of this paper is to investigate the university information professionals (UIPs) preferred modes of soft skills learning and differences in their opinions based on gender, designations and experience. Design/methodology/approach: Quantitative research design using a questionnaire was used for data collection. Data were analyzed through SPSSS version 20.0, using descriptive and inferential statistics. The population of the study included all the UIPs working in the central libraries of the general public sector 33 universities in Pakistan, with nearly a population of 560. Findings: The major findings showed that "mentoring sessions by experts" was the most preferred mode of soft skills learning followed by "learning from colleagues". It showed that UIPs preferred to learn soft skills from experts and colleagues. Independent-samples t -test results found that "mentoring session by experts" was more preferred by females than males. A one-way ANOVA results found significant differences of opinion regarding the "mentoring session by experts" method between librarians and assistant librarians ( p = 0.044). Results were statistically significant also between more experienced and less experienced regarding "real project/assignment-based method" and "mentoring session by experts". In addition, for "formal online courses" and "self-training through reading books", results were statistically significant between experienced groups of 1-5 years and 11-15 years. Overall results indicated that from UIPs' perspective, soft skills should be taught to them using face-to-face methods. Originality/value: This is the first study in Pakistan that dealt with the preferred modes of soft skills learning of UIPs by using a large group ( N = 372) of respondents.